Mapping and modelling malaria risk areas using climate, socio-demographic and clinical variables in Chimoio, Mozambique - Ferrão, João L. (2018)
Ferrão, J. L., Niquisse, S., Mendes, J. M., & Painho, M. (2018). Mapping and modelling malaria risk areas using climate, socio-demographic and clinical variables in Chimoio, Mozambique. International Journal of Environmental Research and Public Health, 15(4), [795]. DOI: 10.3390/ijerph15040795